Immunogenicity of a Dendrimer B2T Peptide Harboring a T-Cell Epitope From FMDV Non-structural Protein 3D - Cañas-Arranz, Rodrigo; de León, Patricia; Forner, Mar; Defaus, Sira; Bustos, María J.; Torres, Elisa; Andreu, David; Blanco, Esther; Sobrino, Francisco (Frontiers in Veterinary Science, 2020)
Synthetic dendrimer peptides are a promising strategy to develop new FMD vaccines. A dendrimer peptide, termed B2T-3A, which harbors two copies of the major FMDV antigenic B-cell site [VP1 (140–158)], covalently linked to a heterotypic T-cell from the non-structural protein 3A [3A (21–35)], has been shown to protect pigs against viral challenge. Interestingly, the modular design of this dendrimer peptide allows modifications aimed at improving its immunogenicity, such as the replacement of the T-cell epitope moiety. Here, we report that a dendrimer peptide, B2T-3D, harboring a T-cell epitope from FMDV 3D protein [3D (56–70)], when inoculated in pigs, elicited consistent levels of neutralizing antibodies and high frequencies of IFN-γ-producing cells upon in vitro recall with the homologous dendrimers, both responses being similar to those evoked by B2T-3A. Lymphocytes from B2T-3A-immunized pigs were in vitro-stimulated by T-3A peptide and to a lesser extent by B-peptide, while those from B2T-3D- immunized animals preferentially recognized the T-3D peptide, suggesting that this epitope is a potent inducer of IFN-γ producing-cells. These results extend the repertoire of T-cell epitopes efficiently recognized by swine lymphocytes and open the possibility of using T-3D to enhance the immunogenicity and the protection conferred by B2T-dendrimers.